The Approach of Al- Qur'an and Hadith Teachers in Teaching Illiterate Students Al-Qur'an at the Islamic State Junior High School in Sigi Regency - nuur, muhammad; Kamaruddin, Kamaruddin; Anirah, Andi (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2024)
This research discusses the analysis of the Qur'an Hadith Teacher's Approach to Illiterate Students of the Qur'an at Islamic Junior High School Alkhairaat Pandere, Gumbasa District, Sigi Regency. This research uses qualitative research methods. The author used observation, interview, and documentation techniques to collect data in the field. Next, the collected data is analyzed using data reduction, presentation, and verification. The results of the research show that the analysis of the Qur'an Hadith Teacher's Approach to Illiterate Students of the Qur'an at Islamic Junior High School Alkhairaat Pandere, Gumbasa District, Sigi Regency includes three points: 1). The learning approach used is a Collaborative Team Games Tournament (TGT) approach and a Two Stay Two Stray collaborative approach. 2). In practice, the teacher uses group learning techniques and writing using Latin letters. 3). Policies taken in cases related to students are always taken by deliberation by the committee and student guardians, and their implementation uses complete supervision from all parties. The implications of this research are expressed in the form of suggestions, namely for the Islamic Junior High School Alkhairaat Pandere to provide more opportunities for Islamic education teachers, especially Qur'an Hadith, to develop their quality in the form of training regarding classroom management, mastery of material and most importantly, deepening and mastering the curriculum and learning approaches which are diverse and continue to develop. Other Islamic junior high schools could adopt the techniques used by the Islamic Junior High School Alkhairaat Pandere in handling students who are illiterate in the Qur'an.